Advanced Modelling and Innovations in Water Resources Engineering Select Proceedings of AMIWRE 2021 - Rao, Chintalacheruvu Madhusudana; Patra, K. C.; Jhajharia, D.; Kumari, Sangeeta; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents select proceedings of the national conference on Advanced Modelling and Innovations in Water Resources Engineering (AMIWRE 2021) and examines numerous advancements in the field of water resources engineering and management towards sustainable development of environment. The topics covered includes river basin planning and development, reservoir planning and management, integrated water management, reservoir sedimentation, soil erosion and sedimentation, agricultural technologies for climate change mitigation, uncertainty analysis in hydrology, water distribution networks, floods and droughts management, water quality modelling, environmental modelling, environmental impact assessment, urban water management, open channel hydraulics, hydraulic structures, groundwater hydraulics, groundwater flow and contaminant transport modelling, computational fluid dynamics, ocean engineering, HEC-RAC, SWAT, MIKE, MODFLOW models applications, numerical analysis in water resources engineering, climate change impacts on hydrology, optimization techniques in water resources, soft computing techniques and applications in water resources and remote sensing / geospatial techniques in water resources. This book will be beneficial for water sectors development mainly agricultural production, reservoir operations, improvement of water quality, flood and drought controls, designing hydraulic structures and geospatial analysis. This book will be a valuable reference for faculties, research scholars, students, design engineers, industrialists, R & D personnel and practitioners working in water resources engineering and its related fields.
Trends of Rainfall and Temperature over Chhattisgarh during 1901-2010 -- Estimation and Simulation of Flows into an Off Taking Canal Using Ansys -- Drought Evaluation of Tiruchirapalli City, India using Three Meteorological Indices -- Forecasting of Meteorological Drought Using Machine Learning -- Assessment of Economic Value of Doddabommasandra Lake Using Contingent Valuation Method and Travel Cost Method -- Meteorological Drought Analysis using SPI-6 for Marathwada Region, Maharashtra State, India -- Analysis and Comparison of Fuzzy Logic and Neural Network based Study for Rainfall Predictions and Hydrological Modelling: A Case Study of Ahmedabad. .
Keywords: Environmental engineering; Civil engineering; Environmental protection; Hydraulic engineering; Environmental Civil Engineering; Soil and Water Protection; Hydraulic Engineering; Water resources development -- Congresses